Cigarette smoking and its effect on coagulation profile, hematological parameters, and oxygen saturation in healthy blood donor - Anshika Srivastava; Kshama Tiwari; Sumaiya Irfan; Noorin Zaidi; Sharique Ahmad; Syed Riaz Mehdi (Asian Journal of Medical Sciences, 2024)
Background: Cigarette smoking causes millions of deaths all around the world each year as it is one of the leading causes of cancer and cardiovascular diseases. Aims and Objectives: The study aimed to study the effect of cigarette smoking on coagulation profile, hematological parameters, and oxygen saturation in healthy blood donors. Materials and Methods: A case–control study was carried out at the Department of Pathology, Era’s Lucknow Medical College which is a tertiary care center, and took place between September 2018 and September 2020 (24 months). Results: Cigarette smoking has adverse effects on hematological parameters (red blood cell count, hemoglobin, hematocrit, mean corpuscular hemoglobin, red cell distribution width, and total leukocyte count) and coagulation profile (prothrombin time, activated partial thromboplastin time, and international normalized ratio). In our study, no adverse effects are seen on oxygen saturation though. Conclusion: Our study shows that hematological parameters and coagulation profile were altered in donors who were smokers and thus, it should be considered during blood donation. Although oxygen saturation was not adversely affected, this study strongly recommends the need for further studies to be done on this parameter of donated blood.